Introduction Indonesian Culture for Chinese Foreign Speakers: Vocabulary and Literacy Development - Sukma Tajuddin; Sukma Sukma; Tri Budianingsih; Dian Sari Unga Waru (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study explores vocabulary and literacy development among Chinese foreign speakers participating in the Bahasa Indonesia untuk Penutur Asing (BIPA) program, particularly within the context of Indonesian cultural education. The data sources were obtained from 46 Chinese students studying at Dalian University of Foreign Languages, Beijing Language and Culture University, Hebei University of Foreign Languages, and Hefei University of Technology. This study employed a qualitative approach to examine the experiences of both instructors and international students in China through in-depth interviews. This study aimed to (1) integrate cultural elements into language instruction to significantly enhance learners’ vocabulary acquisition and cultural literacy and (2) promote effective teaching strategies to enhance learners’ engagement and motivation. This study underscores the importance of a culturally contextualized curriculum in fostering meaningful language-learning experiences and offers practical recommendations for improving the BIPA program. Ultimately, this research contributes to a deeper understanding of the interplay between language and culture in foreign language education.